2009
DOI: 10.1007/s10495-009-0388-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformational similarity in the activation of caspase-3 and -7 revealed by the unliganded and inhibited structures of caspase-7

Abstract: Caspase-mediated apoptosis has important roles in normal cell differentiation and aging and in many diseases including cancer, neuromuscular disorders and neurodegenerative diseases. Therefore, modulation of caspase activity and conformational states is of therapeutic importance. We report crystal structures of a new unliganded conformation of caspase-7 and the inhibited caspase-7 with the tetrapeptide Ac-YVAD-Cho. Different conformational states and mechanisms for substrate recognition have been proposed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Caspase-7 is another executioner caspase that is closely related to caspase-3, with highly similar structure and function (34). We observed that NK cells expressing granulysin in the absence of granzyme B mediated enhanced activation of caspase-7, implicating it in granulysin-induced cell-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 75%
“…Caspase-7 is another executioner caspase that is closely related to caspase-3, with highly similar structure and function (34). We observed that NK cells expressing granulysin in the absence of granzyme B mediated enhanced activation of caspase-7, implicating it in granulysin-induced cell-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 75%
“…It has been proposed that the presence of inhibitor or substrate triggers flipping of the L2′ loop. 34 In support of this hypothesis, apo-crystal structures of caspase-3 and caspase-7 obtained in the presence of inhibitor 35,36 showed that the L2′ loop folded against the L2 and L4 loops. This was in contrast to the zymogen-like conformation of the L2′ loop in the previously reported apocaspase-7 structure crystallized in the absence of inhibitor.…”
Section: The L2′ Loopmentioning
confidence: 79%
“…31 Obviously, the inhibitor-bound species of caspase-9 is different than for caspase-8, and therefore a comparison of the mechanisms is difficult on the basis of the presently available data. Rearrangements upon inhibitor binding in the executioner caspase-3 are limited to side chains of three hydrophobic residues lining the S2 pocket and no loop stabilization was observed 33,34 in contrast to the more extensive changes in capase-8. To what extent the unbound structure of caspase-3 differs from the zymogen cannot be assessed, as no structural information on the proform is available.…”
Section: Discussionmentioning
confidence: 89%
“…We therefore speculate that the increased overall stability of caspase-8 upon addition of the inhibitor is due to rigidification of the loops around the active site and possibly may also involve loop 4 and 5, which in procaspase-8 undergo conformational exchange. 22 Structures for inhibitor-free caspases have also been determined for caspase-3 33,34 and -9. 31 Caspase-9 belongs to the initiator caspases, and the proenzyme is monomeric, indicating that the mechanism of action might be highly similar to the one of caspase-8.…”
Section: Discussionmentioning
confidence: 99%